Six co-occurring conifer species in northern Idaho exhibit a continuum of hydraulic strategies during an extreme drought year. Issue 5 (23rd September 2019) - Baker, Kathryn V; Tai, Xiaonan; Miller, Megan L; Johnson, Daniel M
Abstract: As growing seasons in the northwestern USA lengthen, on track with climate predictions, the mixed conifer forests that dominate this region will experience extended seasonal drought conditions. The year of 2015, which had the most extreme drought for the area on record, offered a potential analogue of future conditions. During this period, we measured the daily courses of water potential and gas exchange as well as the hydraulic conductivity and vulnerability to embolism of six dominant native conifer species, Abies grandis, Larix occidentalis, Pinus ponderosa, Pinus monticola, Pseudotsuga menziesii and Thuja occidentalis, to determine their responses to 5 months of record-low precipitation. The deep ash-capped soils of the region allowed gas exchange to continue without significant evidence of water stress for almost 2 months after the last rainfall event. Midday water potentials never fell below −2.2 MPa in the evergreen species and −2.7 MPa in the one deciduous species. Branch xylem was resistant to embolism, with P 50 values ranging from −3.3 to −7.0 MPa. Root xylem, however, was more vulnerable, with P 50 values from −1.3 to −4.6 MPa. With predawn water potentials as low as −1.3 MPa, the two Pinus species likely experienced declines in root hydraulic conductivity. Stomatal conductance of all six species was significantly responsive to vapour pressure only in the dry months (August–October), with no response evident in the wet months (June–July). While there were similarities among species, they exhibited a continuum of isohydry and safety margins. Despite the severity of this drought, all species were able to continue photosynthesis until mid-October, likely due to the mediating effects of the meter-deep, ash-capped silty-loam soils with large water storage capacity. Areas with these soil types, which are characteristic of much of the northwestern USA, could serve as refugia under drier and warmer future conditions. Abstract : As trees photosynthesize, using carbon from the atmosphere to grow and store energy, they also lose water to the air. When soils dry during a drought, continuing to photosynthesize and lose water puts trees at risk of damaging their hydraulic conductivity and overall health. Six conifer species in northern Idaho changed their hydraulic strategies during a record-breaking drought in 2015. All species more tightly regulated their water use in response both to how dry the air was (vapour-pressure deficit) and to how dry the leaves themselves became (leaf water potential) after 2 months without rainfall.